Knowledge of special education teachers' on learning disabilities/ Nur Nadira Aiza Nasharuddin and Rosilah Wahab - Nasharuddin, Nur Nadira Aiza; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Learning disability is commonly related to reading disability, mathematical disability, writing disability, sensory disability and problems with visual-spatial, intuitive, organizational, evaluative and holistic processing functions. Special education teachers need to do effective, efficient and quality screening and assessment services for identification of children with learning disabilities. T There is a lack of information about the knowledge among special education teachers on learning disabilities .Aim of this study is to identify the level of knowledge on learning disabilities among special education teachers. This was a cross-sectional study, 94 participants in integrated primary schools in Petaling Perdana District, Selangor were participated in this study. The questionnaire consists of socio-demographics items and Knowledge Questionnaire on Learning Disabilities. The results shows 76 participants (80.9%) showed that majority of the special education teachers are in the average level of knowledge on learning disabilities. There are no significant differences in the level of knowledge on learning disabilities with all socio-demographic data.